Knowledge about healthcare associated infections in postgraduate residents from a venezuelan university - Armando Guevara; Abraham Figuera (Kasmera, 2018)
A descriptive, cross-sectional study was carried out with field design to evaluate the knowledge about the healthcare associated infections (HCAI) and its prevention in postgraduate residents of the School of Health Sciences "Dr. Francisco Battistini Casalta” of the Universidad de Oriente, Venezuela. The sample consisted of 51 residents’ physicians from different postgraduate programs. A survey was applied to investigate knowledge on three specific areas: generalities about HCAI, standard precautions and hand hygiene. They were considered to have adequate knowledge if they obtained an average score of 17.5 points or more. 58.8% of the respondents were female with an average age of 31 years (SD ±4.32, Range: 25-47). The average score in the survey was 17.9 points (SD ±1.87, Range: 12-22). The 56.87% approved the survey. When evaluating the knowledge about the studied areas, it was found that the majority have basic concepts about standard precautions (86.27%) but not about generalities of IAAS (37.25%) or hand hygiene (19.6%). In conclusion, the postgraduate residents have adequate knowledge about the HCAI and its prevention but present deficiencies in specific aspects.